自動二輪車乗車用ヘルメットの保護性能についての比較・検討(Comparison of the protective performance of motorcycle helmets: based on experiments of helmet shock absorption and a questionnaire survey of emergency medical centers): －ヘルメット衝撃吸収実験と救命救急センターへのアンケート調査から－. Issue 3 (March 2015) - (Yasumasa Sekine), 関根 康雅; (Manabu Nemoto), 根本 学; (Yoshitaka Ooya), 大谷 義孝; (Shuji Takahira), 高平 修二
ABSTRACT: [Background] Helmets for motorcycles, including motorbikes, are known to be effective head protection. However, there are many motorcycle accident patients transported to emergency medical departments for head trauma, despite wearing a helmet. In Japan, motorcycle helmets are divided into two types on the basis of Japanese Industrial Standards (JIS), the first being helmets for motorcycles with an engine displacement of ≤125cc and the second for helmets unrelated to engine displacement. The objective of this study was to compare the protective performance of these helmets through practical experiments and fact–finding surveys. [Subjects and Methods] Practical experiment: A shock absorption test of JIS type 1 and 2 helmets was performed under identical conditions. The helmets were placed on a human head model and dropped to free fall from the height at which the estimated speed at collision was 20km/h and 28km/h while measuring the shock acceleration inside the helmet during collision. Fact–finding survey: Survey forms on motorcycle accidents, including whether helmets were worn, that occurred during the 3–month period from May 1 to July 31, 2013, were distributed to 30 emergency medical centers in Japan. [Results] Practical experiment: At the estimated speed of 20km/h, the shock acceleration was 223 ± 2.5G for the type 1 helmet and 205 ± 3.2G for the type 2 helmet. At the estimated speed of 28km/h, the shock acceleration was 352 ± 2.8G for the type 1 helmet, in excess of the 300G believed to cause serious injury to the brain, and 232 ± 3.2G for the type 2 helmet. Fact–finding survey: Answers were obtained for 302 patients. Half or more of the accidents happened in an intersection, and over 60% were caused by collisions with vehicles. In addition, the helmet came off as a result of shock during collision in 34.3% of cases with the JIS type 1 helmets. Also, head trauma was observed in 31.3% of the 162 patients whose helmets did not come off. [Conclusion] Head injuries decreased in correlation with protective performance and protective range, so the protective performance of JIS type 1 hardly measures up to the laws established to mitigate trauma. We hope that by dissemination of these findings, they will become one of the determination criteria a consumer uses when purchasing a helmet.